The clinical utility of procainamide‐induced late potentials on the signal averaged ECG. Issue 12 (26th October 2021) - Pearman, Charles Michael; Walia, Jagdeep; Alqarawi, Wael; Larsen, Jacob Moesgaard; Leach, Emma; Krahn, Andrew D.; Laksman, Zachary
Abstract: Background: Late potentials (LPs) identified on the signal averaged electrocardiogram (SAECG) are a marker for an increased risk of arrhythmias in Brugada syndrome (BrS). Procainamide is a sodium channel blocker used to diagnose BrS. The effects of Procainamide on the SAECG in those with BrS and the significance of Procainamide‐induced LPs are unknown. Methods: Procainamide provocation was performed for suspected BrS with 12‐lead and SAECG pre‐ and post‐infusion. Filtered QRS duration (fQRSd), duration of low amplitude signals <40 μV (LAS40) and root‐mean‐square voltage in the terminal 40 ms (RMS40) were determined. Results: Data from 150 patients were included in the analysis (mean age 44.5 years, 109 males). Procainamide increased fQRSd (Pre 118.8 ± 10.5 ms, post 121.2 ± 10.2 ms, p  < 0.001) and LAS40 (Pre 38.7 ± 9.8 ms, post 40.2 ± 10.5 ms, p  = 0.005) and decreased RMS40 (Pre 24.6 ± 12 ms, post 22.8 ± 12 ms, p  = 0.002). LPs were present in 68/150 (45%) at baseline. Fifteen patients with negative baseline SAECGs had LPs unmasked by Procainamide, but six patients had LPs at baseline that were no longer present following Procainamide. Comparing those with normal hearts ( n  = 48) to those with a final diagnosis of BrS ( n  = 38), Procainamide prolonged fQRSd to a greater extent in those with BrS. Comparing those with Procainamide‐induced LPs to those with no LPs at any time did not highlight any aspect of phenotype and did not correlate with a history of ventricular arrhythmias. Conclusions: Procainamide influences the SAECG, provoking LPs in a small proportion of patients. However, there is no evidence that Procainamide‐induced LPs provide additional diagnostic information or aid risk stratification.